2017
DOI: 10.1136/bmjgast-2016-000105
|View full text |Cite
|
Sign up to set email alerts
|

Advanced endoscopic imaging in gastric neoplasia and preneoplasia

Abstract: Conventional white light endoscopy remains the current standard in routine clinical practice for early detection of gastric cancer. However, it may not accurately diagnose preneoplastic gastric lesions. The technological advancements in the field of endoscopic imaging for gastric lesions are fast growing. This article reviews currently available advanced endoscopic imaging modalities, in particular chromoendoscopy, narrow band imaging and confocal laser endomicroscopy, and their corresponding evidence shown to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Open access the widespread adoption of high-resolution endoscopy platforms has dramatically improved the level of mucosal detail visible to the endoscopist, and advanced imaging modalities such as narrow-band imaging (NBI) can improve visual contrast to better examine fine mucosal features. 5 It is recognised that H. pylori naïve, infected or eradicated states, may be associated with distinct mucosal appearances, and the clinical utility of identifying these patterns is an area of ongoing study. 6 With adequate accuracy, it could be appropriate to either initiate eradication therapy for suspected H. pylori, or identify patients at higher risk of long-term complications, that is, those with current or previous H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Open access the widespread adoption of high-resolution endoscopy platforms has dramatically improved the level of mucosal detail visible to the endoscopist, and advanced imaging modalities such as narrow-band imaging (NBI) can improve visual contrast to better examine fine mucosal features. 5 It is recognised that H. pylori naïve, infected or eradicated states, may be associated with distinct mucosal appearances, and the clinical utility of identifying these patterns is an area of ongoing study. 6 With adequate accuracy, it could be appropriate to either initiate eradication therapy for suspected H. pylori, or identify patients at higher risk of long-term complications, that is, those with current or previous H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…There is less evidence to support other methods of virtual CE such as i-Scan digital contrast and flexible spectral imaging color enhancement (FICE). There are currently insufficient data to recommend routine clinical use of these techniques, even though in theory and after proper training they could have similar applications [47,59]. A few prospective studies suggested that blue laser imaging may achieve similar results to NBI [60 -62].…”
Section: Recommendationmentioning
confidence: 99%
“…A few prospective studies suggested that blue laser imaging may achieve similar results to NBI [60 -62]. Other emerging technologies, such as confocal endomicroscopy, endocytoscopy, Raman spectroscopy, and polarimetry, may have a future role but at this stage cannot be recommended for routine clinical use [59].…”
Section: Recommendationmentioning
confidence: 99%
“…Other advanced endoscopic techniques, including confocal microscopy, chromoendoscopy with or without magnification, and Raman spectroscopy, have all shown very high sensitivity and specificity for the detection of IM with area under the curve >0.90, but their expense, complexity (adding to procedural time) and steep learning curve have limited their uptake and utility in clinical practice [71][72][73][74]. Other advanced endoscopic techniques, including confocal microscopy, chromoendoscopy with or without magnification, and Raman spectroscopy, have all shown very high sensitivity and specificity for the detection of IM with area under the curve >0.90, but their expense, complexity (adding to procedural time) and steep learning curve have limited their uptake and utility in clinical practice [71][72][73][74]. There are two major schools of thought regarding the need for non-targeted mapping biopsies in addition to careful endoscopic assessment with the targeted biopsies of suspicious lesions outlined above.…”
Section: Endoscopic Featuresmentioning
confidence: 99%